MODERN CAPABILITIES OF IMMUNOPROPHYLAXIS OF ACUTE RESPIRATORY INFECTIONS IN FREQUENTLY AILING CHILDREN - N.A. Korovina; A.L. Zaplatnikov; I.V. Lepiseva; A.V. Suzdalenkov; A.A. Girina (Union of pediatricians of Russia, 2008)
Literature data analysis and results of the authors' research of reasons and initiating agents of recurrent infections in children are presented. The data on modern opportunities for specific and nonspecific immunological prophylaxis in sickly children are summarized. The results of prophylactic and therapeutic efficiency of ribosomal immunization in children are presented. The typical prophylactic effect of this treatment in children with recurrent respiratory infections and its preventive use as part of a complex program of preparation of children for attending preschool institutions, is established. At the same time, the risk reduction of development of recurrent respiratory infections in the adaptation and the following periods of children's presence in organized collectives, is observed. High therapeutic efficiency of ribosomal immunization for sickly children is demonstrated.Key words: children, immunity, immunological prophylaxis, acute respiratory infections, recurrent respiratory infections, ribosomal immunological prophylaxis, sickly children.